Water Stage and Discharge of a Supraglacial Stream in Southwest Greenland (67.15N, 50.00W) Each Minute from July 13, 2019 to August 10, 2019 - Sasha Leidman; Åsa Rennermalm; S. McKenzie Skiles; Rohi Muthyala (Arctic Data Center, 2023)
A small supraglacial stream in Southwest Greenland was observed for a 29-day period during the melt season of 2019. A Solinst Levellogger pressure transducer continuously measured stage height every minute throughout the observation period. The logger was placed in a RACO-2 metal project box filled with rocks with conduit holes knocked out to allow water to easily flow through. The box was anchored to a PVC pole drilled into the thalweg of the stream channel. Stage heights were corrected for atmospheric presssure using a Solinst Barologger located 2 m above the ice surface of the adjacent shore. Water heights were also collected with a meter stick at the location of the logger periodically throughout the field season in order to correct for measurement drift and systematic instrumentation error. The measurements showed that water level varied between 0.02 and 0.36 meter (m) fluctuating diurnally. Daily averaged water level peaked on August 1st. Additionally to the water stage heights, stream discharge was recorded with a Sontek FlowTracker2 Handheld Acoustic Doppler Velocimeter on 33 occasions throughout the observation period. Measurements were used to create a rating curve relating stage to discharge in an exponential relationship. The relationship was used to extrapolate stream discharge every minute for the 29-day period. This dataset contains the following files: 1. 660_Stage_Data_Downstream_Manual_Corrected; Time series of barometric pressure, water pressure, water level, and interpolated discharge for the study period. 2. Velocity_Data_2019_published; Summary data of velocity and stream geometry measurements collected with the Acoustic Doppler Velocimeter 3. Depth_Velocity_SiteX_Profile_MMDDYYYY; Detailed stream velocity and geometry measurements for each of the 57 site where X is the site number This data is further described in Leidman et al., 2023.